Investigation of corrosion void formation in a Ni-based alloy under simulated MSW incineration condition - Xinxin Wu; Terrence Wenga; Wenchao Ma (Journal of Materials Research and Technology)
Waste incineration has become a new trend for disposing and treating municipal solid waste (MSW). However, due to high chlorine content and alkali metals in waste fractions, waste incinerators suffer severe high-temperature corrosion. The corrosion often accelerates at specific sites forming voids that persist for a long period without being detected, leading to component failure and are less understood, especially in waste incinerators. Therefore, in this study, corrosion void formation and migration mechanism on a newly designed alloy (Ni–28Cr–13Al–5W-0.06B-0.005C) was investigated and the corrosion rate of the alloy was compared with that of Ni–20Cr alloy under simulated municipal solid waste (MSW) incineration conditions at 600 °C. The conditions consisted of 500 ppm HCl, 50 mg/cm2 NaCl, and 100 ppm SO2, 8 vol% O2, and 20 vol% H2O. The pre-and post-exposure sample characterization for the void formation was conducted using XRD, XPS, SEM, EDX, and FIB-TEM. The results show that the mass gain for the Ni–20Cr alloy reached 4.55 mg/cm2 while the mass gain for the Ni–28Cr–13Al–5W-0.06B-0.005C alloy was only 0.65 mg/cm2 over 50 h. Voids and pits were observed at the alloy/oxide interface and were filled with corrosion products. The alloying elements had varied distribution patterns across the voids with Ni and W elements being immobile and mainly occurring in the base substrate while Cr and Al undergo selective removal and diffuse to the surface, leading to the formation of a porous Ni/W-enriched layer. In the presence of Na salt Al was more active in the formation of the oxide scale while in the absence of Na salt Cr was more active. The pore grows and migrates into the alloy through the grain boundary resulting in an internal oxidation attack. The findings provide significant guidance in the development of alloys with better corrosion resistance.